Quantifying current and future risks of invasiveness of non‐native aquatic species in highly urbanised estuarine ecosystems—A case study of the River Neretva Estuary (Eastern Adriatic Sea: Croatia and Bosnia–Herzegovina). (6th November 2020) - Glamuzina, Branko; Tutman, Pero; Glamuzina, Luka; Vidović, Zoran; Simonović, Predrag; Vilizzi, Lorenzo
Abstract: Biological invasions are a major driver of global environmental change as invasive non‐native species can exert severe environmental impacts on invaded ecosystems. Estuaries are especially vulnerable to biological invasions, which in highly urbanised areas are further facilitated by introduction pathways linked to commercial activities. This study provides a risk screening of non‐native invasive species for the highly urbanised River Neretva Estuary (Eastern Adriatic Sea: Croatia and Bosnia–Herzegovina). In total, 12 species of non‐native aquatic organisms were identified and screened for their invasiveness with the Aquatic Species Invasiveness Screening Kit. Of these species, eight were classified as carrying a high risk of invasiveness under current climate conditions and nine under future climate conditions. Amongst the high‐risk species, blue crab Callinectes sapidus has already caused impacts in the risk assessment area, where it also represents an important economic resource. The "horizon" species Pacific oyster Crassostrea gigas and Manila clam Ruditapes philippinarum also carried a high risk of invasiveness, which for the latter species applied under predicted global warming. The present findings will contribute towards preventative management and control measures for the conservation of the natural ecosystem of the River Neretva Estuary whilst accounting for aquatic farming demands.